Super paramagnetic iron oxide contrast-enhanced magnetic resonance imaging was useful in differentiating an insulinoma from an accessory spleen: a case report with review of literature - Ema Toyokuni; Hiroshi Okada; Goji Hasegawa; Mayuko Kadono; Sayaka Kato; Mari Yoneda; Michiaki Fukui (Endocrine Journal)
When a neuroendocrine tumor with abundant blood flow is located in the pancreatic tail, it is difficult to distinguish it from accessory spleen. The patient was a 71-year-old woman who was admitted with impaired consciousness and hypoglycemia, raising suspicion of insulinoma. The selective arterial calcium injection test suggested a lesion in the pancreatic tail. Contrast-enhanced computed tomography and magnetic resonance imaging (MRI) showed a mass in the splenic hilum; however, its continuity with the pancreas was unclear. Contrast-enhanced MRI using super paramagnetic iron oxide (SPIO) showed no SPIO uptake in the splenic hilar mass. SPIO contrast-enhanced MRI is considered useful for differentiating pancreatic endocrine tumors from paraspleen tumors.